Optimasi Formula Tablet Ekstrak Daun Yakon (Smallanthus sonchifolius (Poepp. & Endl.) H. Robinson) Dengan Bahan Pengikat Gelatin Dan Bahan Penghancur Metilselulosa Dengan Metode Simplex Lattice Design - Wuryaningtyas, Bidara Ayuna; , Erindyah R. Wikantyasning, Ph.D., Apt. (2017)
Previous study showed that hydroethanolic extract of yacon leaves (Smallanthus sonchifolius (Poepp. & Endl.) H. Robinson) at the dose of 100 mg/kgBB/day can cause lowered blood sugar levels of rats. The purpose of this study are to determine the effect of variations in the concentration of binder (gelatin) and disintegrant (methylcellulose) on the physical properties of granules and tablets also to determine the concentration of binder (gelatin) and disintegrant (methylcellulose) to obtain the optimum formula of extract yacon leaves tablet. Tablet were formulated using Simplex Lattice Design method with various concentration of gelatin and methylcellulose (2% : 10%, 4% : 8%, 6% : 6%, 8% : 4%, dan 10% : 2%). Optimization of formulas was conducted by Design Expert program 10.0.3.1 (trial). The parameters included were flow rate, the angel of repose, tapped density, uniformity of weight, hardness, friability, and disintegration time. The optimum formula was further verified and analyzed using One Sample T-Test. The result showed that the optimum formula was combination of gelatin 2% and 10% methylcellulose. There was no significant differences between the results of prediction and the results of the verification, this is shown by value of p > 0,05 from flow rate, the angel of respose, tapped density, uniformity of weight, hardness, friability, and disintegration time. It can be concluded that the result is valid.